2007
DOI: 10.1590/s1676-06032007000300015
|View full text |Cite
|
Sign up to set email alerts
|

Reprodução e alimentação de Rhamdia quelen (Quoy & Gaimard, 1824) em rios do Núcleo Santa Virgínia, Parque Estadual da Serra do Mar, São Paulo, SP

Abstract: O objetivo do trabalho foi determinar a época de reprodução, a fecundidade, o tipo de desova e os aspectos alimentares de Rhamdia quelen em rios da Mata Atlântica no Núcleo Santa Virgínia, Parque Estadual da Serra do Mar, estado de São Paulo. Foram realizadas amostragens mensais de janeiro a dezembro de 2004 em dois rios, Paraibuna e Grande, da bacia do rio Paraíba do Sul. A atividade alimentar, o acúmulo de gordura na cavidade visceral e a época reprodutiva ocorreram ao longo de praticamente todo o período de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
6

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(25 citation statements)
references
References 16 publications
0
19
0
6
Order By: Relevance
“…In A. nuchalis, females matured at larger sizes than males, a pattern found in other auchenpterids (Freitas et al, 2011;Santos et al, 2013) as well as many other tropical fishes (Barbieri et al, 2004;Nunes et al, 2004;Gomiero et al, 2007;Rodrigues-Filho et al, 2011;Prudente et al, 2015). In this case, size differences between males and females at first maturity may be related to reproductive competition, with males investing in early maturation in order to be ready to reproduce as soon as possible, ensuring the perpetuation of their genes.…”
Section: Discussionmentioning
confidence: 68%
“…In A. nuchalis, females matured at larger sizes than males, a pattern found in other auchenpterids (Freitas et al, 2011;Santos et al, 2013) as well as many other tropical fishes (Barbieri et al, 2004;Nunes et al, 2004;Gomiero et al, 2007;Rodrigues-Filho et al, 2011;Prudente et al, 2015). In this case, size differences between males and females at first maturity may be related to reproductive competition, with males investing in early maturation in order to be ready to reproduce as soon as possible, ensuring the perpetuation of their genes.…”
Section: Discussionmentioning
confidence: 68%
“…Estudos realizados com R. quelen nos rios de Paraíbuna e Grande da bacia do Paraíba do Sul, também constataram que a espécie apresenta o mesmo tipo de reprodução que o presente estudo (GOMIERO et al, 2007).…”
Section: Resultsunclassified
“…Essa mesma preferência da espécie R. quelen, já foi evidenciada em um trecho do rio Bonito no município de São Domingos, Santa Catarina, tendo uma predominância de 66% da sua dieta (GUERINI et al, 2014). Entretanto foram feitas análises estomacais na mesma espécie, em rios do núcleo Santa Virgínia no parque Estadual da Serra do Mar, São Paulo e verificou-se que o seu hábito alimentar é onívoro (GOMIERO et al, 2007).…”
Section: Figura 3 Representação Do Número De Estômagos Encontrados Dunclassified
“…Gomiero et al (2007) has identified 19 food items in two rivers of the Atlantic forest presenting a higher importance within the stomach contents of this species and some vegetal material, suggesting its diet to be omnivorous, but predominantly carnivorous. Casatti (2002), by studying this species in a first order stream (São Carlos Stream) registered a high consummation of Araneae, Hymenoptera, some vegetal and Trichoptera and On the other hand, in larger aquatic systems the species uses to consume in a higher importance autochthonous items.…”
Section: Discussionmentioning
confidence: 99%
“…Many references related to parameters about biological information to R. quelen are missing or are quite disperse at the specific literature (Gomes et al, 2000), as most of such references are directed to pisciculture and rearing under artificial situations (Gomiero et al, 2007), as the species is considered to be important for pounding in southern Brazil (Behr et al, 1999;Pereira et al, 2006). As references about the natural diet of the species are scarce, mainly by the fact that the species uses to live in many distinct habitats, the main goal of this study is to compare the food use of individuals in four distinct lotic systems.…”
Section: Introductionmentioning
confidence: 99%